(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2022)
Hydroacoustic technology was able to quantify the seabed substrate and can be estimated accurately and near real time on the acoustic characters of each substrate. The purpose of research is to quantify the acoustic backscatters of the seabed substrate in an effort to devolop marine information technology. Data acquisition was using the Simrad EK-15 Single Beam Echosounder acoustic instrument set at a frequency of 200 kHz. Data processing and analysis includes acoustic backscatter strength, sediment type, acoustic bottom backscattering computation of seabed substrate and spatial analysis of seabed acoustic backscatter in the Lancang Island waters. The results of this study indicate that the acoustic backscatter values of the seabed substrate based on the SS value and particle size at each sampling station are -21.08 to -24.55 dB for type of substrate sands, fine sands are -25.67 to -26.67 dB, and very fine sands ranging from -27.42 to -28.03 dB. Based on the range of acoustic backscatter values ​​obtained from the sampling stations, type of seabed substrates along the survey line are very coarse sand, coarse sand, medium sand, fine sand, very fine sand, coarse silt, medium silt, fine silt, coarse clay and fine clay in the range values ​​of -47.85 to -17.07 dB. Sand substrates were dominant over silt and cly at the study site. Acoustic backscatter strength is strongly influenced by particle size, morphology and seabed relief.